Stability of a colloidal system based on avocado (Persea americana Mill. cv. Hass) and others : effect of process and composition (2017)
ABSTRACT: Avocado (Persea americana Mill. cv. Hass), is a perishable fruit, which compositionally presents nutritional benefits, which has led to its productive chain to look for new alternatives of agroindustrialization to improve its competitiveness in the market, being guacamole a potential option. The aim of this research was to evaluate the influence of composition and homogenization process on the colloidal system stability based on avocado and other ingredients for a potential use in the aspersion drying process. We used the surface response methodology and a central composite experimental design for experimental optimization of the process, considering three independent variables as follows: avocado dry solids (DSavocado), homogenization time and tert-butylhydroquinone concentration (TBHQ), and six dependent variables: zeta potential (-ζ), color (L *: brightness, a *: green-red chromaticity, b *: yellow-blue chromaticity), viscosity (µ), spectral absorption stability index, peroxide index (PI) and particle size (D10, D50 and D90). The best emulsion and process formulation was achieved with 47.1% of DSavocado, 5 min of homogenization and 100 mg.kg-1 of TBHQ, obtaining an emulsion with -ζ = -27.67 ± 0.29, L * = 51.3 ± 1.0, a * = -5.8 ± 0.8 and b * = 30.0 ± 1.9, µ = 1034.56 ± 95.91 cP , R = 0.78 ± 0.03, IP = 0.73 ± 0.30 meq H2O2.Kg-1 emulsion, D10 = 8.1 ± 0.7 µm, D50 = 56.2 ± 11.5 µm and D90 = 346.6 ± 94.6 µm. The emulsion based on avocado and other ingredients, presents a physico-chemical, physical stability adequate stability, which guarantees a potential use for aspersion-drying process, since it meets with the criteria design for viscosity and total solids, of the pilot unit PSALAB, Vibrasec S.A.